2013
DOI: 10.3390/v5102601
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Molecular Diversity of Spike Gene of Porcine Epidemic Diarrhea Virus in China

Abstract: Since late 2010, porcine epidemic diarrhea virus (PEDV) has rapidly disseminated all over the China and caused considerable morbidity and high mortality (up to 100%) in neonatal piglets. 79.66% (141 of 177) pig farms in 29 provinces (excluding Tibet and Hainan, China) and 72.27% (417 of 577) samples were positive for PEDV confirmed by reverse transcription-polymerase chain reaction (RT-PCR). The full-length S genes of representative field strains were sequenced. 33 field strains share 93.5%–99.9% homologies wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
78
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(83 citation statements)
references
References 23 publications
5
78
0
Order By: Relevance
“…The S gene exhibits a high degree of genetic diversity [5, 20, 21], and the S protein plays important roles in interactions with cellular receptors during virus entry, the induction of neutralizing antibodies in natural hosts, growth adaptation in vitro, and attenuation of virulence in vivo [22]. Thus, the PEDV S glycoprotein is utilized for determining genetic relatedness among PEDV isolates and developing diagnostic assays and effective vaccines [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…The S gene exhibits a high degree of genetic diversity [5, 20, 21], and the S protein plays important roles in interactions with cellular receptors during virus entry, the induction of neutralizing antibodies in natural hosts, growth adaptation in vitro, and attenuation of virulence in vivo [22]. Thus, the PEDV S glycoprotein is utilized for determining genetic relatedness among PEDV isolates and developing diagnostic assays and effective vaccines [23, 24].…”
Section: Introductionmentioning
confidence: 99%
“…The PEDV genome is composed of the 5′ untranslated region and at least seven open reading frames (ORFs) that encode four structural proteins, namely spike (S), envelope (E), membrane (M) and nucleocapsid (N), and three major non‐structural proteins (1a, 1ab and ORF3) (Song & Park, ). Of the structural proteins, the S glycoprotein is the most diverse protein (Chen et al., ), and it plays a vital role in the induction of neutralizing antibodies and regulation of interactions with cellular receptors to mediate virus entry (Bosch, van der Zee, de Haan, & Rottier, ). It is also associated with growth adaptation in vitro and attenuation of virulence in vivo (Sato et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…67 The results of many studies based on sequencing and phylogenetic analyses showed that these PEDV isolates with high virulence circulating in the People's Republic of China were new variants and differed genetically from the prototype CV777 strain. 11,59,[67][68][69][70][71][72][73][74][75][76][77][78] Now, PED became endemic; however, it remains the most devastating enteric disease leading to serious losses in the People's Republic of China. PED outbreaks in the People's Republic of China from late 2010 were caused by at least three genotypes, including genotypes IIa, IIb, and Ib.…”
Section: Asiamentioning
confidence: 99%